Change of emotional experience in major depression and borderline personality disorder during psychotherapy: associations with depression severity and personality functioning - Dinger, Ulrike; Fuchs, Magdalena; Köhling, Johanna; Schauenburg, Henning; Ehrenthal, Johannes C. (Journal of personality disorders, 2021)
This study examines emotional experience in major depressive disorder (MDD) with and without comorbid borderline personality disorder (BPD). It investigates if depression severity or personality functioning mediates group differences and which aspects of emotional experience change during psychotherapy. The emotional experience of MDD-BPD patients (n = 44) was compared to MDD-only patients (n = 35) before and after multimodal short-term psychotherapy. Emotions were classified based on valence and an active/passive polarity. MDD-BPD patients exhibited more active-negative emotions. This group difference was mediated by the level of personality functioning, but not by depression severity. Although passive-negative emotions decreased and positive emotions increased during therapy, there was no significant change in active-negative emotions. The two patient groups did not significantly differ in the change of emotional experience. Lower levels of personality functioning in depressed patients with BPD are associated with a broader spectrum of negative emotions, specifically more active-negative emotions.
Gesehen am 14.04.2021